RESPONSIBLE ATTITUDE TO THE HEALTH FOR PUPILS FROM THE CENTER FOR SOCIAL AND PSYCHOLOGICAL REHABILITATION: THEORETICAL FOUNDATION - Krupnyk, Zoriana I. (Educological discourse, 2015)
In the article the theoretical analysis of the concept of «health», «attitude», «responsible attitude», «formation», «healthy lifestyle»; presented the features of formation of the responsible attitude to health in socio-psychological rehabilitation. The activity of socio-psychological rehabilitation in Ukraine to ensure the formation of a responsible attitude to the health of pupils aged 6 to 15 years.